STRENGTH ANALYSIS OF GLUED-IN STEEL RODS WITH DIFFERENT LOCATIONS IN CLT PANELS CROSS SECTION - Bidakov, Andrii; Raspopov, Ieugeniy; Pustovoitova, Oksana; Strashko, Bogdan (Academic journal Industrial Machine Building Civil Engineering, 2019)
New types of wood based building materials to which the CLT refers require an accurate evaluation of the strength of varioustypes of connections. CLT panels connections with glued-in steel rods are of interest due to the possibility of creating quickmounted and rigid joints in the factory. Since the CLT have the structure of the perpendicular orientated boards in adjacentlayers, the strength and behaviour of the pasted rods is difficult to predict. The purpose of this study was to establish thestrength of the glued-in rods by pull-pull tests with different locations relative to the boards layers in the cross-section of theCLT panel. Diameter of all considered steel rods was smaller than thick of timber planks 30 mm in 5-lyers CLT specimenswithout gaps and stress relieves. Anchored length of rods in all specimens was 100 mm by using two component epoxy adhesive system.
Keywords: cross laminated timber; CLT; connection; glued-in steel rods; joint; prefabricated panels; strength by pull-pull tests